2018
DOI: 10.1097/ijg.0000000000000825
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Trabecular Microbypass Stent With Cataract Extraction in Severe Primary Open-angle Glaucoma

Abstract: Trabecular microbypass stent implantation during cataract surgery safely and effectively lowers IOP and medication use in patients with severe primary open-angle glaucoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 14 publications
2
25
0
Order By: Relevance
“…In addition, the proportion of eyes with IOP ≤15 mmHg nearly doubled versus preoperative (81% at 24 months versus 42% preoperatively). Consistent with prior studies evaluating IOP-lowering treatments, 10,[15][16][17]46,47 eyes with higher baseline IOP achieved a more robust postoperative IOP reduction than eyes with lower baseline IOP. Also consistent with prior MIGS studies, 16,17,48 our data suggested a slight diminution of IOP-and medication-reducing effects after the first year postoperative.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In addition, the proportion of eyes with IOP ≤15 mmHg nearly doubled versus preoperative (81% at 24 months versus 42% preoperatively). Consistent with prior studies evaluating IOP-lowering treatments, 10,[15][16][17]46,47 eyes with higher baseline IOP achieved a more robust postoperative IOP reduction than eyes with lower baseline IOP. Also consistent with prior MIGS studies, 16,17,48 our data suggested a slight diminution of IOP-and medication-reducing effects after the first year postoperative.…”
Section: Discussionsupporting
confidence: 82%
“…To date, the safety and performance of iStent trabecular micro-bypass have been established by a breadth of studies evaluating the device, including in standalone implantation or in combination with cataract surgery or other MIGS procedures, in both single-and multiple-stent usage, in populations with various levels of disease severity, and in various subtypes of glaucoma and ocular hypertension. [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] The stent has been widely adopted and studied by surgeons around the world. 43 However, iStent outcomes have not been as closely examined in Japanese populations.…”
Section: Discussionmentioning
confidence: 99%
“…The observed 2.7 mmHg IOP reduction should be appreciated in the context of the cohort’s relatively low mean starting IOP, given that lower starting IOP usually results in smaller postoperative IOP reductions. 16 , 17 , 29 , 42 , 43 The IOP target of ≤15 mmHg was achieved in half-again more eyes at two years versus preoperative (77% vs 49%, p<0.001). Coinciding with this IOP reduction, there was a threefold decrease in mean medication burden (0.49 versus 1.49 medications, p<0.001).…”
Section: Discussionmentioning
confidence: 91%
“…Compared with the previously published outcomes of the surgeon's stent-cataract experience, in which IOP was reduced by 37% and medications were reduced by 68% [46], the IOP and medication reductions in this stand-alone cohort were slightly higher (42% and 82% reductions, respectively). Possible reasons for this difference include the higher preoperative IOP in the stand-alone cohort, as this is known to produce greater postoperative IOP reductions [27,29]. The preoperative medication burden also was higher in the stand-alone cohort, which may predispose to greater reductions in medication number if the end goal is the same for a given patient (0 or 1 medication, for example).…”
Section: Discussionmentioning
confidence: 99%
“…To date, this device has amassed a sizable longterm evidence base regarding its safety and performance in eyes with open-angle glaucoma, in settings both with and without cataract surgery. Most studies of the device have assessed outcomes in mild to moderate glaucoma [17][18][19][20][21][22][23][24][25][26][27], but other patient populations increasingly have been the subject of evaluation, such as pseudoexfoliative glaucoma, severe or refractory glaucoma, or newly diagnosed, treatment-naïve glaucoma [28][29][30][31][32][33]. Another growing and relevant area of investigation has been economics outcomes research [34][35][36][37][38][39], which consistently has shown favorable cost-effectiveness of the iStent in various healthcare models around the world.…”
Section: Introductionmentioning
confidence: 99%